First report on dwarf x dwarf coconut (Cocos nucifera L.) hybrids at cyclonic east coastal region of India - Arunkumar, R.; Surulirajan, M.; Senthilkumar, N.; Irene vethamoni, P.; Niral, V.; Sumitha, S.; Jerard, B. A. (Journal of Plantation Crops, 2025)
Coconut, an important commercial plantation crop of India, is extensively grown from the state of Gujarat in the West Coast to West Bengal in the East Coast along the coastal lines of Peninsular India and is spreading inland over the non-traditional areas. The increased demand for fresh consumption and tender coconuts led the breeders towards development of dwarf hybrids for the benefit of the farming community. With this objective an experiment was initiated during 2011 to study the feasibility of growing D x D hybrids. The dwarf hybrids exhibited trunk height of i.e.3.8 to 5.5m height at 13 years of age. The tender fruit weight ranged between 741.43g (DDCH 3) to 1180.33g (DDCH 4). In DDCH 4, the yield of endosperm (57 liters) was also significantly higher than the check (22.65 liters) which indicate the prolific yield for beverage purpose. The PCA analysis of reproductive parameters revealed that, the total inflorescence per palm, number of spikelets per palm, number of male and female flowers per inflorescence had positive contribution (PC1). With higher yield and better quality parameters, the hybrid DDCH 4 was first D x D hybrid observed to be suitable for the East Coast region of Tamil Nadu.